Cost efficiency in halal logistics: A DEA-based evaluation of Malaysian logistics providers - Mohd Nor, Haslina; Mat Yunoh, Muhammad Naqib (International Journal of Accounting, Finance and Business, 2025)
Halal logistics is a growing niche within the global supply chain, driven by increasing consumer demand for Shariah-compliant services. However, its implementation often incurs higher operational costs due to segregation requirements and certification processes. This study investigates cost-efficiency among Malaysian Halal logistics companies using Data Envelopment Analysis (DEA). By analysing inputs such as truck units and warehouse space against contract logistics value, the study identifies inefficiencies and proposes strategies for optimization. It uses both qualitative (interviews and observation) and quantitative (Data Envelopment Analysis, or DEA) approaches. The study also extends existing theories by incorporating religiosity factors, which refers to the implementation of Syariah principles in managing Halal products. The findings show that logistics costs arise from the segregation of Halal and non-Halal products and from having dedicated trucks or warehouses. The research findings can be beneficial for companies and authorities to improve Halal logistics activities and address issues raised by Halal logistics companies.